2012
DOI: 10.1007/978-1-61779-992-1_15
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics-Based Identification and Analysis of Cis-Regulatory Elements

Abstract: Summary Identification of cis-regulatory elements, such as enhancers and promoters, is very important not only for analysis of gene regulatory networks but also as a tool for targeted gene expression experiments. In this chapter, we introduce an easy but reliable approach to predict enhancers of a gene of interest by comparing mammalian and Xenopus genome sequences, and to examine their activity using a co-transgenesis technique in Xenopus embryos. Since the bioinformatics analysis utilizes publically availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…The genomic Nkx3.1 locus contains a candidate enhancer region for the mouse prostate, which is located at −7 kb from the 3′-coding region of Nkx3.1 ( 46 ). Using the rVISTA genome browser and MultiPipmaker ( 47 ), we found that the 3′-region of Nkx3.1 was conserved among mammals but not in other vertebrates (data not shown). The conserved region was illustrated by a comparison of the human, mouse, and opossum loci ( Figure 5 H), which contained several Smad-binding elements.…”
Section: Resultsmentioning
confidence: 99%
“…The genomic Nkx3.1 locus contains a candidate enhancer region for the mouse prostate, which is located at −7 kb from the 3′-coding region of Nkx3.1 ( 46 ). Using the rVISTA genome browser and MultiPipmaker ( 47 ), we found that the 3′-region of Nkx3.1 was conserved among mammals but not in other vertebrates (data not shown). The conserved region was illustrated by a comparison of the human, mouse, and opossum loci ( Figure 5 H), which contained several Smad-binding elements.…”
Section: Resultsmentioning
confidence: 99%
“…These results prompted us to investigate whether Mafb is a direct target gene of AR signaling during urethral masculinization. To identify androgen response regions in the Mafb locus, we compared its sequences in mice and other species using the ECR browser (34). Mafb is composed of 1 exon, and its CDS is significantly conserved among many vertebrate species.…”
Section: Ar Signaling Regulates Mafb Expression Through the Mafb 3utrmentioning
confidence: 99%
“…In order to identify regulatory sequences that activate Hnf1b gene expression in the developing kidney, we searched for evolutionary conserved non-coding sequences (CNSs) as candidates for enhancers. Using in silico methods that allow detailed inspection of sequence conservation profiles across several genomes 29 , we compared the genomic sequence of a 157 kb segment encompassing the mouse ( Mus musculus ) Hnf1b gene with the orthologous intervals in human ( Homo sapiens ), rat ( Rattus norvegicus ), opossum ( Monodelphis domestica ), chicken ( Gallus gallus ), frog ( Xenopus tropicalis ) and zebrafish ( Danio rerio ). This analysis identified one CNS (called CNS1) conserved in all species, except zebrafish, located 33.4 kb upstream the Hnf1b transcription start site in mouse and a second one (CNS2) located in the 4 th intron of Hnf1b conserved in all species examined (Fig.…”
Section: Resultsmentioning
confidence: 99%